Climate change indirectly reduces breeding frequency of a mobile species through changes in food availability. Issue 4 (8th April 2019) - Mastrantonis, Stanley; Craig, Michael D.; Renton, Michael; Kirkby, Tony; Hobbs, Richard J.
Abstract: Trends of environmental change are influencing the behavior of many species across the world, while highly mobile species are disproportionately impacted by climate change and human modification. Here, we investigate the mechanisms behind climate change effects on the reproductive traits of highly mobile, West Australian bird taxa, the forest red‐tailed black cockatoo Calyptorhynchus banksii naso (FRTBC). Using a dataset of annual breeding frequency spanning 19 yr, in combination with hydrological, climatological, and remotely sensed data, we modeled the effects of environmental variation on the annual breeding frequency of FRTBCs. We found several significant relationships between annual breeding frequency of FRTBCs and environmental variation. While the model, which included a proxy for the availability of the cockatoo's primary food source and the previous season's rain, explained 49% of annual breeding frequency, there were also direct and indirect effects of heatwaves and forest productivity. Forest red‐tailed black cockatoo breeding appears to be linked to the spatiotemporal availability of its primary food sources, the fruit from the tree species, marri Corymbia calophylla and jarrah Eucalyptus marginata . However, Western Australia is experiencing significant climate change, with increases in temperature and declines in rainfall altering the phenologies of these species, while declining rainfall is affecting the vegetation structure of the region. As drought events and temperatures are anticipated to increase over the region, it is expected that the food resources during the breeding season for cockatoos will become increasingly limited in time and space, thus threatening the persistence of this iconic species. This scenario is likely to be representative of many other situations where wide‐ranging species rely on patchy food resources in a changing environment. As global biodiversity is increasingly threatened, this study presents timely evidence illustrating how climate change is affecting the persistence of a threatened, mobile species, and what the implications are for mobile species around the world.